Extracellular vesicles in pancreatic cancer immune escape: Emerging roles and mechanisms - Chunping Liu; Dongyue He; Longmei Li; Shihui Zhang; Lei Wang; Zhijin Fan; Yichao Wang (Elsevier, 2022)
Pancreatic cancer (PC) is the most lethal malignancy worldwide due to its delayed diagnosis and limited treatment options. Despite great progress in clinical trials of immunotherapies for various cancers, their effectiveness in PC is very low, indicating that immune evasion is still a major obstacle to immunotherapy in PC. However, the mechanism of immune escape in PC is not fully understood, which substantially restricts the development of immunotherapy. As an important component of intercellular communication networks, extracellular vesicles (EVs) have attracted increasing attention in relation to immune escape. This review aims to provide a better understanding of the roles of EVs in tumor immune escape and the potential to expand their application in cancer immunotherapy. The relationship between PC and the tumor immune microenvironment is briefly introduced. Then, the mechanism by which EVs are involved in immune regulation is summarized, and the latest progress in determining the role of EVs in regulating PC immune escape is highlighted.